CLASH-VLT: constraints on f (R) gravity models with galaxy clusters using lensing and kinematic analyses - Pizzuti, Lorenzo; Amendola, Luca (Arxiv, 2017)
We perform a maximum likelihood kinematic analysis of the two dynamically relaxed galaxy clusters MACS J1206.2-0847 at $z=0.44$ and RXC J2248.7-4431 at $z=0.35$ to determine the total mass profile in modified gravity models, using a modified version of the MAMPOSSt code of Mamon, Biviano and Bou\'e. Our work is based on the kinematic and lensing mass profiles derived using the data from the Cluster Lensing And Supernova survey with Hubble (hereafter CLASH) and the spectroscopic follow-up with the Very Large Telescope (hereafter CLASH-VLT). We assume a spherical Navarro-Frenk-White (NFW hereafter) profile in order to obtain a constraint on the fifth force interaction range $λ$ for models in which the dependence of this parameter on the enviroment is negligible at the scale considered (i.e. $λ=const$) and fixing the fifth force strength to the value predicted in
Gesehen am 09.11.2017